The Influence of Law Number 1 of 2004 concerning State Treasury on State Financial Management - Fahri, Achmad; Simanjuntak, Sandy Wiratno H; Mahardika, Dutasena; Putra, Moody Rizqy Syailendra (CV. Rayyan Dwi Bharata, 2025)
Various efforts have been made to realize good governance in the presentation of reports, accountability, and management of government finances, including the birth of Law Number 1 of 2004 concerning State Treasury. The purpose of this study is to determine the influence of Law No. 1 of 2004 concerning State Treasury on the management of state finances and the principles of state financial management according to Law No. 1 of 2004 concerning State Treasury. The results of this study are that the State Treasurer General who holds the position of Minister of Finance has the authority to supervise and manage government accounts. The State General Cash Account is opened by the Minister of Finance to manage government accounts. Implementation of the state budget, management of state cash, development of financial management of public service agencies, accounting and financial reporting, and management of government investment are the five main components of the treasury administration process. Clarity of Roles and Check and Balance are two main principles of the State Treasury Law. The State Treasury Law adheres to the principles of universality, annuality, unity, and specialization.